PENGARUH CORE SERVICE QUALITY, PERIPHERAL SERVICE QUALITY DAN CITRA DESTINASI TERHADAP KEPUASAN KONSUMEN DALAM MENINGKATKAN MINAT LOYALITAS PADA BAHARI DAMPO AWANG BEACH TAMAN REKREASI PANTAI KARTINI REMBANG - Lely Afiati (Jurnal Bisnis dan Kewirausahaan, 2016)
Quality of service and customer satisfaction is an important factor for a business. Consumer satisfaction is feeling happy someone arising from comparing the performance the perception by the service or the results against those expectations. If the performance fails to meet expectations, customers will be dissatisfied. If performance in line with expectations, the customer will be satisfied. Therefore, this study analyzed the effect kuaitas core services, peripherals and services to customer satisfaction destination image, due to indications of dissatisfaction visitors with the services provided by the Dampo Awang Beach Kartini Beach Recreation Park Rembang. Samples were visitors Dampo Awang Beach Kartini Beach Recreation Park in Rembang district, Central Java. By using purposive sampling technique. Collecting data in this study using a questionnaire. Data was analyzed using SEM analysis with AMOS program 18. The test results and analysis of the model shows that all hypothesis of the research is unacceptable, Core Service Quality (HI) positive and significant impact on customer satisfaction with the value of 2.451. Peripheral Service Quality (H2) positive and significant impact on customer satisfaction with the value of 2.201. Citra Destinations (H3) positive and significant impact on customer satisfaction with a score of 3.67. Core Service Quality (H4) positive and significant impact on the interest Loyalty to the value of 2.37. Peripheral Service Quality (H5) positive and significant impact on the interest Loyalty to the value of 2.193. Citra Destinations (H6) positive and significant impact on the interest Loyalty to the value of 2.11. Customer Satisfaction (H7) positive and significant impact on the interest Loyalty with a value of 2.5.